Mitigation of earthquake hazards of medium-rise buildings by using different soil improvement methods - Gültekin, Furkan. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2023., 2023)
Earthquakes can be hazardous to occupants and their assets, especially in some regions such as Turkey, Japan, Chile, and the United States of America etc. Nowadays, some regulations were published to mitigate the hazards occurring in buildings during earthquakes. Besides, the hazards can be mitigated by making use of different soil improvement methods such as Geotechnical Seismic Isolation (GSI) Systems which earthquake loads transferred from ground to structure are decreased using geotechnical materials. Gravel and Gravel-Rubber Mixtures (GRM) can be alternative materials for the GSI system because they provide more bearing capacity, less earthquake-induced settlements and high permeability. The aim of this thesis is to evaluate the effectiveness of the proposed Gravel and Gravel Rubber Mixtures (GRM) materials on the seismic performance of low-to medium rise buildings by means of 1/10 scaled 3 and 5- story building models by shaking table tests. The shaking table experiments were conducted by considering different rubber content, thickness of GSI and the number of stories under various seismic motions. Within the scope of this thesis, all improved cases were compared with unimproved cases. This study showed that surrounding building foundations with Gravel or Gravel Mixtures plays a key and favorable role in the mitigation of earthquake hazards by dissipating earthquake energy inside the soil.
Keywords: Hazardous geographic environments.; Earthquake resistant design.; Buildings -- Earthquake effects.